U- and E-Service, Science and Technology International Conference, UNESST 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - Kim, Tai-hoon (Communications in Computer and Information Science, 2011)
This book constitutes the refereed proceedings of the International Conference, UNESST 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of u- and e-service, science and technology.